Evaluate: 8x-(2x-1)=3x-11

Expression: $8x-\left( 2x-1 \right)=3x-11$

When there is a $-$ in front of an expression in parentheses, change the sign of each term of the expression and remove the parentheses

$8x-2x+1=3x-11$

Collect like terms

$6x+1=3x-11$

Move the variable to the left-hand side and change its sign

$6x+1-3x=-11$

Move the constant to the right-hand side and change its sign

$6x-3x=-11-1$

Collect like terms

$3x=-11-1$

Calculate the difference

$3x=-12$

Divide both sides of the equation by $3$

$x=-4$